Theatre as a Form of Greatness - BOLDEA, Iulia (Studia Universitatis Babeș-Bolyai Dramatica, 2020)
In her attempt of proving the theatricality of the theatre, Maria Vodă Căpuşan cultivates a solidly assimilated bibliography, as well as last minute analytical instruments. Her essays have a predominantly theoretical nature, referring less to a certain play or performance, and more to the theatrical phenomena, with its fundamental dimensions and conceptualizations. The author believes that the mythical scripts of the 20th century drama conserve their modelling and integrative functions regardless of the denying passion of different literary, avant-garde or simply modernist movements. Within her books, Maria Vodă Căpușan offers theoretical syntheses worthy of interest from the perspective of new methodological and epistemological approaches applied with a critical discernment and inconspicuous erudition.